Truth, Lie, and Fake News in Lula’s and Bolsonaro’s Speeches: An Analysis of Meanings from the Candidates’ Twitter in the Campaign for President of Brazil in 2022 (Global Journal of Human-Social Science, 2024)
The research monitored mentions of the terms fake news truth and lie in the publications of the candidates Lula and Bolsonaro on their Twitter profiles during the electoral campaign for president in the Brazilian elections of 2022 in order to understand the meanings produced in their speeches following the French Discourse Analysis methodology Contemporary studies about disinformation on digital platforms bring the theoretical problematization of concepts As a result we have a rhetorical posture in Jair Bolsonaro s posts to reinforce a particular view of truth and lie no citations were found for the term fake news On the other hand Lula seeks to confirm the integrity of his statements or reiterate the falsity of what his opponent says using discursive techniques similar to those of professional fact-checkers concentrating all citations on the expression fake news in the research corpus
Keywords: fake news; disinformation; truth; lie; lula; bolsonaro